Nurse Practitioners' Attitudes and Knowledge about Influenza Immunization - Kim Curry; Christina Humphreys (University of North Florida, 2014)
Influenza remains a leading cause of death nationally and internationally. Annual influenza immunization for healthcare workers has been recommended since 1984. Despite this, many healthcare workers do not receive the immunization. Nurse practitioners (NPs) are key primary care providers in the U.S. healthcare system. The purpose of this study was to assess the knowledge and personal beliefs of NPs as a step toward understanding the reasons for the participation or non-participation in the influenza vaccine of this professional group. A quantitative cross-sectional survey of knowledge, attitudes, NP demographics, and patient factors was carried out. Most of the 174 participants had received the vaccine. Vaccine status was not correlated with the assessed risk level of patients. Available and mandatory vaccine in the workplace was correlated with vaccination status of the NP. Vaccine status of the NP was correlated with patient counseling to receive influenza immunization. Not all NPs agree with or adhere to federal vaccine recommendations. It is critically important for healthcare providers to base decisions affecting the health of themselves and their patients on evidence-based research.